The Influence of Liturgical Music and Song on Congregation of Saint Cornelius Madiun Church at 2019 - Rif’at Husnul Ma’afi; Dzakiyyah Fauziyah Rif’at (Journal of Comparative Study of Religions)
Music has an important role in the Catholic act of worship. Liturgy, as the main act of worship, has always been using music and song to increase the number of its. Saint Cornelius Madiun Church as one of the Surabaya diocese has a big development in accord to the number of the congregation since its establishment. This parish has three thousand congregations and still increasing annually. One of these factors is caused by the unique music and song served by the ministry of the church. This research is field research and employed the phenomenological approach to analyze the data. The result is that the liturgical music and song which are played in Saint Cornelius Madiun Church are in accord with what has been determined by the Council Vatican 2, namely Sacrosanctum Concilium about liturgical Music. Both are music as a part of the liturgy, and music as accompaniment music during liturgy. The music and the song of the liturgy give big influence in creating a sense of solem, sacred, humility and delighted in living up to the liturgy of the mass because music has a variety of tempo, rhythm, and a style adapted to the liturgical activities. Besides, the lyrics of the song become the main factor to touch the heart of the congregation and expresses the intention that wants to be conveyed by the performed music.